2018
DOI: 10.1177/0269881118784872
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride modulation of carbon dioxide hypersensitivity and thermal nociceptive hypersensitivity induced by interference with early maternal environment

Abstract: Single-dose nebulized amiloride decreased repeated cross-fostering animals' carbon dioxide sensitivity and nociception indices to levels that were no different from those of control animals. Inasmuch as these results pertain to human anxiety and/or pain hypersensitivity, our findings provide a rationale for studying inhaled amiloride in some anxiety disorders and/or pain syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…A clinical implication of the environmental covariation is that some early‐life adversities (You, Albu, Lisenbardt, & Meagher, 2018) could increase liability to both anxiety and pain. Preclinical, genetically‐informed models of co‐occurring anxiety, pain, and early‐life adversities are beginning to provide leads about etiological mechanisms including gene‐environment interplay (Cittaro et al, 2016; Giannese et al, 2018), and new somatic treatments (Battaglia, Rossignol, Bachand, D'Amato, & De Koninck, 2019) that may constitute alternatives to current conceptualizations and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical implication of the environmental covariation is that some early‐life adversities (You, Albu, Lisenbardt, & Meagher, 2018) could increase liability to both anxiety and pain. Preclinical, genetically‐informed models of co‐occurring anxiety, pain, and early‐life adversities are beginning to provide leads about etiological mechanisms including gene‐environment interplay (Cittaro et al, 2016; Giannese et al, 2018), and new somatic treatments (Battaglia, Rossignol, Bachand, D'Amato, & De Koninck, 2019) that may constitute alternatives to current conceptualizations and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of comparative human and preclinical studies of responses to CO 2 (an unconditioned stimulus that evokes panic-like responses in humans at risk for panic disorder and hyperventilation in rodents) [5][6][7][8][9][10], we reported that life adversities enhance the liability to anxiety and pain through the enrichment of acid-sensing ion channel (ASIC) genes -1 and -2 [11][12][13]. Coherent with these findings, ASIC-antagonist amiloride normalizes the enhanced anxious and nociceptive responses that are proper of mice exposed to early disrupted maternal care and the nociceptive responses of rats that underwent prenatal maternal stress [12,14]. In a series of randomized human clinical trials, amiloride was shown to be safe and effective in humans for the treatment of cystic fibrosis following inhalational administration [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is a combined chemoreceptive/nociceptive stress-induced molecular modification that has been observed in the medulla oblongata where the protection centers around the response to CO 2 -induced cerebral acidosis that leads to ACIS1-protective modification in respiration and nociception. Where epigenetically predisposed GAD and panic disorders are correlated with elevated CO 2 levels as induced in utero or as the result of ELF-associated choking or suffocation, the blockade of the ACIS1 gene with amiloride may be considered as a potential pharmacotherapeutic intervention [29]. The key point derived from this study is that environmental stress induces a neuroepigenomic response that may instantiate pCO 2 levels and reconditioning toward psychiatric conditions (e.g., GAD) in adults.…”
Section: Epigenetics Of the Early Uterine Environment And Potential Fmentioning
confidence: 94%
“…Such early life adversities (ELFs) as maternal stress during pregnancy have been correlated to both anxiety disorders and the potential for the experience of pain throughout life. A recent paper has linked animal model carbon dioxide exposure and subsequent hypersensitivity to ELF-associated anxiety [29]. In this study, mice were cross-fostered in an atmosphere enriched to 6% CO 2 in the presence or absence of an acid channel ion sensing 1 gene (ACIS1) blockade drug called amiloride.…”
Section: Epigenetics Of the Early Uterine Environment And Potential Fmentioning
confidence: 99%